2013
DOI: 10.1037/a0031545
|View full text |Cite
|
Sign up to set email alerts
|

Male Role Norms Inventory–Short Form (MRNI-SF): Development, confirmatory factor analytic investigation of structure, and measurement invariance across gender.

Abstract: The current study reports the development from the Male Role Norms Inventory-Revised (MRNI-R; Levant, Rankin, Williams, Hasan, & Smalley, 2010) of the 21-item MRNI-Short Form (MRNI-SF). Confirmatory factor analysis of MRNI-SF responses from a sample of 1,017 undergraduate participants (549 men, 468 women) indicated that the best fitting "bifactor" model incorporated the hypothesized 7-factor structure while explicitly modeling an additional, general traditional masculinity ideology factor. Specifically, each i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
344
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 202 publications
(371 citation statements)
references
References 31 publications
16
344
4
1
Order By: Relevance
“…Information on these measures follows, and additional information on the MRNI-SF, CMNI-46, and GRCS-SF is reported in Citation masked. (Levant et al, 2013) is derived from the MRNI-R and measures the endorsement of TMI. As noted in the Introduction above, the MRNI-SF has seven subscales, each with three items.…”
Section: Methodsmentioning
confidence: 99%
“…Information on these measures follows, and additional information on the MRNI-SF, CMNI-46, and GRCS-SF is reported in Citation masked. (Levant et al, 2013) is derived from the MRNI-R and measures the endorsement of TMI. As noted in the Introduction above, the MRNI-SF has seven subscales, each with three items.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to being significantly shorter, the MRNI-SF has demonstrated good fit in a confirmatory factor analysis (CFA) measurement model of the seven subfactors and more advanced models specifying simultaneous influences of the seven subfactors and a general TMI factor (Levant et al, 2013). Specifically, Levant and colleagues (2013) tested two competing measurement models for the MRNI-SF which included a broad TMI factor: a second-order factor structure and a bifactor structure.…”
Section: Factor Structure Of the Mrni-sfmentioning
confidence: 99%
“…In the past 30 years, counseling psychologists have made significant advancements in the measurement of masculinity-related constructs, such as gender role conflict (O'Neil 1981(O'Neil , 2008, conformity to masculine norms (Mahalik et al, 2003) and masculinity ideologies (Levant, Hall, & Rankin, 2013;Levant, Hall, Weigold, & McCurdy, 2015). Most notably, investigators have identified that men internalize masculinity ideologies, consisting of socially constructed beliefs about what men should think, feel, and do.…”
mentioning
confidence: 99%
See 2 more Smart Citations